Does Remittance Inflow and Foreign Direct Investment Spur Economic Development in Developing Countries? Insights from Nigeria - MBA, Peter N.; CHIJIOKE, Mercy I. (Theoretical and Practical Research in Economic Fields, 2024)
Given the rising inflows of remittance and foreign direct investment into developing countries, the study examined their importance on economic development in Nigeria using the ordinary least squares method and time series data collected from secondary sources, and the Error correction models (ECM) were estimated. Findings showed that remittances and foreign direct investment impacted positively and significantly on economic development and the exchange rate negatively influenced economic development. Thus, recommended that the government should remove strict transaction costs of remitting money to expand the overall inflow of remittances and more personal remittances should be encouraged for investment in human capital development. Additionally, improvement in the investment climate for existing and expected foreign investors, relaxation of the strict laws on profit repatriation, and the improvement in the macroeconomic environment by curbing security challenges, social unrest, and corruption will encourage foreign investors to increase their investments. It also recommends that the government take advantage of these inflows to stabilize the volatility of the exchange of the domestic currency.